2016
DOI: 10.1253/circj.cj-16-0332
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography of De Novo Lesions and In-Stent Restenosis in Coronary Saphenous Vein Grafts (OCTOPUS Study)

Abstract: Background:The OCTOPUS registry prospectively evaluates the procedural and long-term outcomes of saphenous vein graft (SVG) PCI. The current study assessed the morphology of de novo lesions and in-stent restenosis (ISR) in patients undergoing PCI of SVG. Methods and Results:Optical coherence tomography (OCT) of SVG lesions in consecutive patients presenting with stable CAD and ACS was carried out. Thirty-nine patients (32 de novo and 10 ISR lesions) were included in the registry. ISR occurred in 5 BMS and 5 DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Our study showed that BVS characterized stable scaffold concentricity up to 48 months after the implantation. It may be explained by the fact that vein graft lesions are less calcified and thus an appropriate scaffold shape was much more easily achieved as compared to native coronary arteries [22, 23]. Additionally, the stable BVS shape may explain the lack of malapposition during the follow-up, which in line with the animal model observations [24], but in contrast to human studies.…”
Section: Discussionmentioning
confidence: 89%
“…Our study showed that BVS characterized stable scaffold concentricity up to 48 months after the implantation. It may be explained by the fact that vein graft lesions are less calcified and thus an appropriate scaffold shape was much more easily achieved as compared to native coronary arteries [22, 23]. Additionally, the stable BVS shape may explain the lack of malapposition during the follow-up, which in line with the animal model observations [24], but in contrast to human studies.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, PCI of SVG is accompanied by high rates of restenosis, 8,9 an independent predictor of long‐time survival 5 . Because of low shear stress and a high thrombogenic state, SVG ISR develop faster than de novo lesions in SVG 25 . However, elapsed time from stent implantation to ISR does not seem to differ between SVG and native vessel lesions, 26 which implicates similar pathophysiological processes causing ISR in SVG and native vessels 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Because of low shear stress and a high thrombogenic state, SVG ISR develop faster than de novo lesions in SVG 25 . However, elapsed time from stent implantation to ISR does not seem to differ between SVG and native vessel lesions, 26 which implicates similar pathophysiological processes causing ISR in SVG and native vessels 25 . Taking these considerations into account, ISR located in SVG constitute a clinically significant challenge in interventional cardiology.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-nine patients hospitalized in the Upper Silesia Medical Center between June 2013 and March 2016 were included in the OCTOPUS registry [ 20 , 21 ]. Each patient gave informed written content, and the study complied with the Declaration of Helsinki and was accepted by the local ethical committee.…”
Section: Methodsmentioning
confidence: 99%